(untitled) (Medical Forum Monthly, 2024)
This, and in the next few issues, I’ll talk about fitness. Considering that I have already touched this topic before, albeit very slightly, in our June 2015 issue, I’ll make this a several part topic, and go through, in depth, about fitness in general, and the trends going the rounds in our country. First of all, let’s see what fitness actually means: ‘the quality or state of being fit1.’ Now keep in mind that there are several types of fitness, namely, physical, mental and emotional. We, for now, we will associate ourselves with only the Physical aspect. Physical fitness accounts for an individual’s ability to carry out a specific task without unnecessary fatigue. Up until recently, fitness has largely been something that we as Pakistanis have generally kept at an arm’s length, but, as of late, the tide has begun to turn. But, the rise in fitness enthusiasts in Pakistan has come after an exponential rise in obesity, westernization of our diet and love for luxury. And even though people are looking to be fit, the rise in the number of people looking to achieve a certain level of fitness, compared to the rising levels of obesity in our country remains abysmal. There remain two integral components of fitness: diet and exercise. Regardless of what anyone claims, these two go hand in hand. Remember, you can’t out train a bad diet. For now let’s just start off with exercise. For starters, let’s see what science has to say about the multitude of benefits exercise has to offer: Controls weight3 Combats health conditions and diseases3 & 5 Improves mood 2, 3 Boosts energy3 Promotes better sleep 3, 4 Now, going through these 5 benefits, and well, these 5 alone, who wouldn’t want these? In more ways than one, exercise is that miracle cure that humankind has sought since its creation. For all its worth, everyone should exercise. Depending on your age and physical abilities, it could merely be a 15 minute walk or a grueling 1.5 hour long weight training session. Regardless, exercising regularly, at least 30 minutes a day, is what most experts recommend to maintain a certain level of fitness. And as far as my opinion and experience with fitness goes, I recommend everyone to exercise, even if you start off with one single step, start exercising. As time will go by, you’ll get better and fitter, and once the results start showing, trust me, you’ll be hooked.